Electrocatalytic conversion of CO2 over in-situ grown Cu microstructures on Cu and Zn foils - Anchu Ashok (14152020) (2021)
Electrochemical conversion of carbon dioxide to value added multi-carbon products is of great importance and a promising approach to mitigate greenhouse gases. In this work, we report the fabrication of electrodes by depositing Cu over the metallic foils of Cu and Zn, which show high faradic efficiency for the conversion of CO2 to formic acid, acetate, and methanol. The morphology, phase and oxidation state of the Cu were different on the two foils while maintaining the same synthesis steps. The Cu particles embedded on Cu foil (Cu/Cu-foil) are in 3D cuboids form with flat and smooth faces, whereas Cu on Zn foil (Cu/Zn-foil) emerge in the shape of 3D flowers with the club of Cu microspikes grown perpendicularly from a root. For the electrocatalytic conversion of CO2, the Cu/Cu-foil shows a high selectivity for formic acid and ethyl acetate with the highest faradaic efficiency of 78 % at −0.3 V vs RHE, and 64 % at −1.0 V (vs RHE) for the two products, respectively. In contrast, the Cu/Zn-foil displays a high selectivity towards methanol, with the highest faradaic efficiency of 48 % at −1.0 V vs RHE, indicating that the product selectivity can be easily modulated by changing the metallic foil on which the Cu particles are deposited. Both the electrodes, Cu/Cu-foil and Cu/Zn-foil, show long-term stable performance while maintaining the selectivity of the products during CO2 electrocatalytic conversion. Other Information Published in: Journal of CO2 Utilization License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jcou.2021.101749